“Maybe that's the landscape that's coming?”: The emergence of writing pedagogies in AI-mediated learning environments - Ott, Mary; Veselka, Mercedes; Cristancho, Sayra; Hibbert, Kathryn; Lingard, Lorelei (Language and Literacy / Langue et littératie, 2026)
The rise of generative artificial intelligence (genAI) has provoked critical questions about what it means to write and how to teach it. Research exploring writing pedagogy post-genAI reflects tensions between deep concerns and hopeful visions. This qualitative study explored the experiences of language and literacy educators (n=39) teaching writing in secondary and post-secondary contexts in Canada. These educators offered insights into the values and strategies underpinning their writing pedagogies and highlighted roles genAI could play as a coach or collaborator depending on instructional goals for learning to write or writing to learn. They also shared how their emerging approaches to teaching writing were influenced by other constituents in their pedagogical landscapes such as student needs, curriculum and assessment frameworks, and institutional policies on student use of AI. Understanding purposes for writing and the ecologies of different education environments opens space to consider the place of genAI in writing as a learning process. This study contributes a framework of instructional goals and a reflective ‘landscapes’ tool to support the agency of language and literacy educators to enact writing pedagogies that empower learners in different AI-mediated learning environments.